Transformações recentes no circuito espacial produtivo de hidrocarbonetos e nas trajetórias da transição energética no Brasil - Luciano Duarte (Caravelle)
This paper’s main purpose is to present a brief analysis of transformations that have taken place in the hydrocarbon production circuit in Brazil, especially after the discovery of large reserves in the Pre-salt. It also seeks to identify how this important event has opened different horizons for an energy transition in Brazil. Finally, it examines the effects provoked by the political crisis around 2010 and the reemergence of neoliberal policies with Bolsonaro’s government upon the dynamics of hydrocarbon circuit and energy transition.